Supervised Machine Learning with Python Develop rich Python coding practices while exploring supervised machine learning - Smith, Taylor (Packt Publishing Limited, 2019)
bTeach your machine to think for itself!/b h4Key Features/h4 ul liDelve into supervised learning and grasp how a machine learns from data /li liImplement popular machine learning algorithms from scratch, developing a deep understanding along the way /li liExplore some of the most popular scientific and mathematical libraries in the Python language /li /ul h4Book Description/h4 Supervised machine learning is used in a wide range of sectors (such as finance, online advertising, and analytics) because it allows you to train your system to make pricing predictions, campaign adjustments, customer recommendations, and much more while the system self-adjusts and makes decisions on its own. As a result, it's crucial to know how a machine " learns under the hood. This book will guide you through the implementation and nuances of many popular supervised machine learning algorithms while facilitating a deep understanding along the way.